TINJAUAN ONTOLOGI, EPISTEMOLOGI, DAN AKSIOLOGI MODEL PEMBELAJARAN MULTILITERASI DALAM PEMBELAJARAN BAHASA INDONESIA - Setiawaty, Rani; Anisa, Devita Rahmatul; Apriliyanto, Muhammad Eko; Sabila, Fadiatus; Tifalia, Khusnul (Alpen: Jurnal Pendidikan Dasar, 2026)
Abstract : This article examines the multiliteracy learning model in Indonesian language learning from ontological, epistemological, and axiological perspectives. The purpose of this study is to understand the nature, methods, values, and benefits of the multiliteracy model in improving students' literacy competencies in elementary schools. The study was conducted using a Systematic Literature Review (SLR) approach on 21 national journals collected from Google Scholar and the Publish or Perish (POP) application published between 2015 and 2025 with the keyword “multiliteracies learning.” Data analysis was conducted in depth to draw conclusions. Based on the analysis results, it was concluded that, ontologically, the multiliteracy model is understood as a holistic approach emphasizing mastery of various literacies (digital, visual, information, media, and critical) as well as critical thinking, collaborative, and communicative skills. From an epistemological perspective, this model emphasizes active learning stages that include pre-activity, core activity, and post-activity, with various strategies centered on exploration and problem-solving. Axiologically, multiliteracy learning has been proven to improve students' reading and writing skills, as well as encourage activity, creativity, and contextual understanding of teaching materials. Thus, this model is relevant for shaping students who are adaptive, critical thinkers, and have broad literacy competencies in the 21st century. Abstrak :Artikel ini mengkaji model pembelajaran multiliterasi dalam pembelajaran Bahasa Indonesia melalui perspektif ontologi, epistemologi, dan aksiologi. Tujuan kajian ini adalah memahami hakikat, metode, serta nilai dan manfaat model multiliterasi dalam meningkatkan kompetensi literasi siswa di sekolah dasar. Kajian dilakukan menggunakan pendekatan Systematic Literature Review (SLR) terhadap 21 jurnal nasional yang dikumpulkan dari Google Scholar dan aplikasi Publish or Perish (POP) terbitan 2015–2025 dengan kata kunci Pembelajaran multiliterasi.Analisis data dilakukan secara mendalam untuk ditarik simpulan. Berdasarkan hasil analisis disimpulkan bahwa, Secara ontologis, model multiliterasi dipahami sebagai pendekatan holistik yang menekankan penguasaan berbagai literasi (digital, visual, informasi, media, dan kritis) serta kemampuan berpikir kritis, kolaboratif, dan komunikatif. Dari sisi epistemologi, model ini menekankan tahapan belajar aktif yang mencakup praaktivitas, aktivitas inti, dan pascaaktivitas, dengan berbagai strategi yang berpusat pada eksplorasi dan pemecahan masalah. Secara aksiologis, pembelajaran multiliterasi terbukti meningkatkan kemampuan membaca dan menulis siswa, serta mendorong keaktifan, kreativitas, dan pemaknaan kontekstual terhadap materi ajar. Dengan demikian, model ini relevan untuk membentuk siswa yang adaptif, bernalar kritis, dan memiliki kompetensi literasi yang luas di era abad ke-21.